2013
DOI: 10.1371/journal.pone.0063580
|View full text |Cite
|
Sign up to set email alerts
|

Olean-12-Eno[2,3-c] [1,2,5]Oxadiazol-28-Oic Acid (OEOA) Induces G1 Cell Cycle Arrest and Differentiation in Human Leukemia Cell Lines

Abstract: Oleanolic acid (3β-hydroxy-olea-12-en-28-oic acid) is a natural pentacyclic triterpenoic acid found in many fruits, herbs and medicinal plants. In the past decade, increasing evidence has suggested that oleanolic acid exhibits inhibitory activities against different types of cancer including skin cancer and colon cancer, but not leukemia. We report here that a derivative of oleanolic acid, olean-12-eno[2,3-c] [1], [2], [5]oxadiazol-28-oic acid (designated OEOA) effectively blocks the proliferation of human leu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 47 publications
(64 reference statements)
1
9
0
Order By: Relevance
“…OA and its derivatives have been shown to exhibit an inhibitory effect on tumor growth in vivo and induce apoptosis in human breast cancer cells [21,22]. The present study demonstrated that SZC014, a novel derivative of OA with improved stability and water solubility, effectively inhibited breast cancer cells growth and enhanced apoptosis induction dose-dependently, as compared with OA.…”
Section: Discussionsupporting
confidence: 49%
“…OA and its derivatives have been shown to exhibit an inhibitory effect on tumor growth in vivo and induce apoptosis in human breast cancer cells [21,22]. The present study demonstrated that SZC014, a novel derivative of OA with improved stability and water solubility, effectively inhibited breast cancer cells growth and enhanced apoptosis induction dose-dependently, as compared with OA.…”
Section: Discussionsupporting
confidence: 49%
“…Investigators have continued to search for and develop drugs that are more selective for effective treatment of leukemia (Döhner et al, 2010;Dores et al, 2012). Among these strategies, apoptosis and differentiation-based targeted therapies have become a research hotspot Gao et al, 2012;Ng et al, 2013;Zhang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Olean-12-Eno[2,3-c] [1,2,5] oxadiazol-28-oic acid (OEOA), synthetic derivative of OA, induced G 1 cell cycle arrest as well as differentiation in human leukemia cell lines, K562, HEL and JURKAT [62]. Three new active oleanolic vinyl bornates inhibited the growth of leukemia cells (Jurkat and K562) and Burkitt’s lymphoma cells (Jijoye) without concomitant inhibition of non-tumoral human fibroblasts [63].…”
Section: In Vitro Effects Of Oa and Its Synthetic Derivatives On Cmentioning
confidence: 99%